Influence Of Person Organizational Fit (PO-Fit) And Employee Engagement In Improving Employee Performance With Organizational Citizenship Behavior (OCB) As Intervening Variables (In Semarang's Police Academy) - Souisa, Johanis (Economics and Business Solutions Journal, 2018)
The purpose of this research is to test and to describe the influence of the person organizational fit and Employee Engagement against employee performance with Organizational Citizenship Behavior as an intervening variable in MANAGE Akpol Semarang. Target research activities are devoted to the modeling of the impact person organizational fit, Employee Engagement against performance employee with Organizational citizenship behavior as intervening variable. The research population is all the government employees in the MANAGE part of the Semarang as many as 100 with sample 100 employees, whereas sample technique used is saturated sample method, the technique of data analysis is done by using double linear regression. Based on an analysis conducted by the researchers concluded that person organizational fit proved to have a positive effect on organizational citizenship behavior, person organizational fit proved to have a positive effect on employee performance. Employee engagement has a positive effect on organizational citizenship behavior, employee engagement has a positive effect on employee performance, person organizational fit is more effective indirectly influencing or through organizational citizenship behavior intervening, Employee engagement is more effective than indirect through intervening organizational citizenship behavior.